Status of Electric Power Sector Reform in Russia - Palamarchuk, Sergei (International Journal of Energy Economics and Policy, 2016)
Restructuring and deregulation of the electric power sector have had a long-term history in many countries. The sector management and Government of each country endeavor to apply positive experience gained by other countries, taking into account technical and economic conditions and features of their own power sector. The paper describes the main characteristics of the power sectors in Russia, as well as concepts and principles of the power sectors liberalization. The main components of the liberalization process, such as the principles of privatization, structure of property, competition promotion and regulation practice are described and can enhance policy learning. Current challenges and urgent trends in following sector modernization are presented. Keywords: Power sector, Electricity market, Regulatory framework JEL Classification: L5